2018
DOI: 10.1177/1748006x18768701
|View full text |Cite
|
Sign up to set email alerts
|

Wind turbine planetary gearbox feature extraction and fault diagnosis using a deep-learning-based approach

Abstract: Planetary gearboxes are widely used in the drivetrain of wind turbines. Planetary gearbox fault diagnosis is very important for reducing the downtime and maintenance cost and improving the safety, reliability, and life span of the wind turbines. The wind energy industry is currently using condition monitoring systems to collect massive real-time data and conventional vibratory analysis as a standard method for planetary gearbox condition monitoring. As an attractive option to process big data for fault diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Tang et al [25] used shift-invariant sparse coding to generate a set of latent components that act as fault filters in a bearing or a gearbox. Moreover, studies by Ahmed et al [26] and He et al [27] proposed classification strategies that use the learned sparse representations on stacked autoencoders and large memory storage and retrieval neural networks, respectively. Further extensions of the work by Liu et al [22] had been developed by Wang et al [28] and Zhou et al [29], who used the same dictionary learning method with different classification strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al [25] used shift-invariant sparse coding to generate a set of latent components that act as fault filters in a bearing or a gearbox. Moreover, studies by Ahmed et al [26] and He et al [27] proposed classification strategies that use the learned sparse representations on stacked autoencoders and large memory storage and retrieval neural networks, respectively. Further extensions of the work by Liu et al [22] had been developed by Wang et al [28] and Zhou et al [29], who used the same dictionary learning method with different classification strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have recommended and demonstrated successfully the use of pre-trained network models. 3137 In the present study, the feature extraction properties of several renowned CNN architectures like VGG 16, 18 GoogLeNet, 38 AlexNet, 17 and ResNet50 20 were evaluated with the help of machine learning classifiers. A brief description of the CNN models considered are described in this section.…”
Section: Machine Learning Based Three Phase Approach For Fault Detection In Aerial Imagesmentioning
confidence: 99%
“…They used auto-encoder residuals for component fault diagnosis and isolation. Another application in wind turbine was presented in He et al (2018) where DL was used for the condition monitoring of the wind turbine planetary gearbox. In this application, the fault features were obtained directly from raw vibration data using DL.…”
Section: Introductionmentioning
confidence: 99%